Generalized tuberculosis with long-term course in the guise of liver cirrhosis - Z. A. Lemeshko; M. V. Mayevskaya; I. N. Tikhonov; N. P. Musina; M. S. Zharkova; Ye. V. Fominykh; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To demonstrate unusual clinical symptoms and difficulties of diagnostics of disseminated tuberculous process.Material and methods. The 25 year-old patient, who was managed for 10 years for liver cirrhosis of nonspecified etiology, was investigated. The careful analysis of clinical presentation of disease, data of physical examination, results of radiological and other methods of diagnostics was carried out.Results. It was possible to suspect and subsequently to confirm disseminated tuberculosis with involvement of the lungs, the heart, pericardium, pleura, mesenteric lymph nodes, the liver; chronic right-sided tubercular pleurisy with pleurocirrhosis; constrictive pericarditis with signs of right ventricular failure; cardiac liver fibrosis (Pick's pseudocirrhosis); mixed portal hypertension.Conclusion. The detailed analysis of clinical presentation of disease, physical data and application of complex of visual and other methods of investigation expand potential of diagnostics of disseminated tuberculous process.